New tick and insect cell line resources for vector-borne disease research from the Tick Cell Biobank - Catherine Hartley; Jing Jing Khoo; Alistair Darby; Benjamin L. Makepeace; Lesley Bell-Sakyi (Revue d'élevage et de médecine vétérinaire des pays tropicaux, 2025)
Background: Arthropod cell lines play an important role in research on the control of vector-borne pathogens of veterinary, medical and agricultural importance. The Tick Cell Biobank (TCB) at the University of Liverpool is the world’s only dedicated collection of cell lines derived from tick and insect vectors of viral, bacterial, protozoan and helminth pathogens. Aim: The TCB in Liverpool and TCB Outposts in Malaysia and Brazil were established to facilitate access for researchers worldwide to tick and insect cell line resources, and training in their maintenance, application and development. Methods: The TCB receives, stores and distributes arthropod cell lines to scientists on request, and generates new cell lines from tick and insect vectors. To facilitate successful uptake of the cell lines, the TCB and its Outposts provide training in arthropod cell culture, and ongoing advice and support to recipients. Cell lines are supplied subject to Material Transfer Agreements. Results: The TCB now houses over 90 cell lines derived from ixodid and argasid ticks, mosquitoes, biting midges, sand flies, tsetse flies, triatomine bugs and honey bees. This paper describes new and recently-developed/acquired resources including cell lines derived from the ticks Argas reflexus, Hyalomma lusitanicum, Hyalomma marginatum and Rhipicephalus bursa, and the insects Anopheles stephensi, Apis mellifera, Culicoides sonorensis, Glossina morsitans, Phlebotomus argentipes and Triatoma infestans. Conclusions: The majority of vector species represented in the collection are of tropical or sub-tropical origin. Through distribution of these existing and new cell lines, the TCB and TCB Outposts will continue to underpin global research on arthropod vectors and the livestock and human pathogens that they transmit.